Pengaruh likuiditas terhadap profitabilitas di bank syariah - Heri Sudarsono; Sarastri Mumpuni Rubha; Ari Rudatin (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study examines the impact of liquidity on Islamic banks profitability during the years from 2014 to 2019. The study extracted its data from the annual reports of six Islamic banks in Indonesia that have been in operations on or before 2014 to 2019. The liquidity model is built from four liquidity variables namely financial to debt ratio (FDR), liquid asset to total asset (LATA) dan liquid assets to deposits (LAD). The results of the study show that FDR is correlated negatively with ROA and NOM, but correlated positively with ROE. Thus, LAD indicate a positive correlation with ROA and NOM. And, LATA found to be significant with ROE at 0,05 Significant level.